The detection of hot cores and complex organic molecules in the Large Magellanic Cloud - Sewiło, Marta; Ward, Jacob L. (The astrophysical journal. Part 2, Letters, 2018)
We report the first extragalactic detection of the complex organic molecules (COMs) dimethyl ether (CH 3 OCH 3 ) and methyl formate (CH 3 OCHO) with the Atacama Large Millimeter/submillimeter Array (ALMA). These COMs, together with their parent species methanol (CH 3 OH), were detected toward two 1.3 mm continuum sources in the N 113 star-forming region in the low-metallicity Large Magellanic Cloud (LMC). Rotational temperatures ( ##IMG## [http://ej.iop.org/images/2041-8205/853/2/L19/apjlaaa079ieqn1.gif] $T_\mathrmrot\sim 130$ K) and total column densities ( ##IMG## [http://ej.iop.org/images/2041-8205/853/2/L19/apjlaaa079ieqn2.gif] $N_\mathrmrot\sim 10^16$ cm −2 ) have been calculated for each source based on multiple transitions of CH 3 OH. We present the ALMA molecular emission maps for COMs and measured abundances for all detected species. The physical and chemical properties of two sources with COMs detection, and the association with H 2 O and OH maser emission, indicate that they are hot cores. The fractional abundances of COMs scaled by a factor of 2.5 to account for the lower metallicity in the LMC are comparable to those found at the lower end of the range in Galactic hot cores. Our results have important implications for studies of organic chemistry at higher redshift.
Gesehen am 22.11.2022